Critical Pedagogy and Equity Promotion in Culturally and Linguistically Diverse Classroom - Surya Sigdel; Mani Ram Sharma (Universitas Bengkulu, 2021)
This paper explores English language teachers’ perception of critical pedagogy and equity promotion in lingo-cultural diverse classroom. The study concerns how the teachers find multicultural students’ problems and address them in the classroom. The study further investigates how teachers use dimensions of equity (multicultural education, social justice education and culturally responsive pedagogy) to promote social harmony, critical awareness and independent learning. In the study, I have used narrative inquiry as a research method, selected six participants purposively from public schools of Kathmandu and collected information from in-depth semi-structured interviews. I have employed multiple layers of thematic analysis, interpreted narrative data and developed six different themes: facility and access, classroom management, language and behavior, classroom activities, feedback and reinforcement and evaluation procedures. On the basis of this study, what I found that school environment, classroom activities, evaluation procedures and feedback and reinforcement are the major factors for the influence of their students’ participation. The school management has major role to facilitate and encourage teachers for the promotion of students centered methods such as project based learning and collaborative learning. Along all these aforementioned themes, teachers have prominent role to run active participatory classroom activities through student friendly activities like language games and healthy academic debate. Not only that, teachers are equally responsible to identify at-risk students and address their issues immediately to promote independent learning. Furthermore, to evaluate students’ progress, intra-personal comparative evaluation procedure is found more effective than inter-personal comparative evaluation procedures to encourage them to strive ahead with self-respect. The study expects relevant recommendations in the field of content-based child-friendly teaching learning activities where students participate actively enjoy the activities and learn from self and others.